The economics of population growth - Simon, Julian Lincoln, 1932-1998 (Princeton legacy library., 2019)
Comparison with stationary and very fast rates of population growth shows modern population grwoth to have long-run positive effects on the standards of living. This is Julian Simon's contention, and he provides support for its validity in both more and less-developed countries. He notes that since each person constitutes a burden in the short run, whether population growth is judged good or bad depends on the importance the short run is accorded relative to the long run. The author first analyzes empirical data, formulating his conclusions using simulation models. He then reviews our knowledge of the effect of economic level upon population growth. A final section of his book considers the framework of welfare economics and values within which population policy decisions are now made. He finds that the implications of policy decisions can prove inconsistent with the values that prompt their recommendation. Julian L. Simon is Professor of Economics and Business Administration at the University of Illinois. Originally published in 1977. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.